Resource Dependence, Recycling, and Trade - Peter H. Egger; Christian Keuschnigg (Center for Economic Studies and ifo Institute (CESifo), 2023)
Recycling waste from used goods can substitute for scarce raw materials and reduce resource dependence. This paper presents a model of waste collection, recycling and final goods production using raw and recycled materials. Non-recycled waste must be safely stored by landfill to avoid environmental damage. The costs of waste disposal create externalities. An optimal allocation requires a trash tax to make producers pay for the costs of waste disposal, and an input subsidy to recycling firms to compensate for the savings in disposal costs. We study trade between resource poor economies exporting final goods, and resource rich countries exporting raw materials. We find rich welfare effects of trade policy with non-trivial interactions between terms of trade effects and distortions in recycling and resource extraction.
Keywords: D62; Q32; Q53; F18; 330; waste; recycling; externalities; resource dependence; trade